Evaluation of hemochemical changes in the blood of piglets supplemented with two microbial preparations - Marín Cárdenas, Alfredo; Marrero Suárez, Leandro Isidoro; García Díaz, Juan Ramón (My University, 2018)
hematological and biochemical blood values of pigs, 120 piglets were used (Duroc/Yorkshire/Landrace), distributed according to a completely randomized design into three groups of 40 animals each: T1) control; T2) microbial preparation A and T3) microbial preparation B. Treatment T2 contained Lactobacillus acidophilus, L. bulgaricus and Streptococcus thermophilus. T3 was composed by T2 microorganisms plus Saccharomyces cerevisiae and Kluyveromyces fragilis (L-4 UCLV). At 14 and 42 days of age of the piglets, samples were taken to evaluate the effect of additives in the hematological profile and blood biochemistry. Values of hemoglobin, hematocrit and erythrocytes, as well as high density lipoproteins were higher (P <0.05) in T3 for both ages of animals. Evaluation of hemochemical changes in the blood of piglets supplemented with two microbial preparations. While, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular concentration and total proteins were lower (P <0.05) in T2 and T3, leukocytes, basophils, eosinophils, albumin, glucose and triglycerides were higher (P <0.05) in the animals of control group. However, values of blood concentration and blood biochemistry were among the normal parameters for this species. It is concluded that the addition of microbial preparations with probiotic activity to the diets of piglets favorably improves the values of the blood and biochemical profile of the blood and, thereby, improves the physiological state and health of the animals.
Keywords: Blood Values; Blood Biochemistry; Young Pigs; Probiotics; Agro-industrial Byproducts